Understanding Sofia’s travel dynamics: Study of private traffic patterns and urban mobility - Lidia Lazarova Vitanova; Evgeny Shirinyan; Tereza Trendafilova; Dessislava Petrova-Antonova (Transportation Research Interdisciplinary Perspectives)
Transportation and mobility provide a foundation for sustainable society, facilitating the efficient movement of people, goods, and services across diverse spatial and temporal scales. They not only support economic activities and enhance social interactions but also enable urban development, global trade, and access to essential resources and opportunities. This study introduces a comprehensive framework for analysing the dynamics of urban transport and travel behaviours related to private vehicles, considering different temporal and spatial dimensions in Sofia, Bulgaria. By integrating high-resolution data from TomTom’s Traffic Stats with Geographic Information Systems (GIS), the study develops an advanced approach that merges various datasets, including traffic flow, density, and energy consumption, thereby facilitating multidimensional assessments of urban challenges at the city level. The significant benefit of this research is its potential for scalability and relevance to other metropolitan areas, especially those encountering comparable issues related to rising urban density, traffic congestion, and environmental pressures. The findings reveal notable traffic fluctuations, with peak congestion during weekday rush hours, particularly concentrated in central business districts and major arterial routes. Persistent congestion areas are also identified on weekdays and weekends, highlighting critical zones requiring infrastructural improvements and optimised traffic management strategies. The results underscore the importance of implementing sustainable urban mobility policies, optimising transport infrastructure, and strategies for climate adaptation.